Targeting neoantigens to APC-surface molecules improves the immunogenicity and anti-tumor efficacy of a DNA cancer vaccine - Barrio-Calvo, Marina; Kofoed, Søren Vester; Holste, Sofie Cens; Sørensen, Anders Bundgård; Viborg, Nadia; Kringelum, Jens Vindahl; Kleine-Kohlbrecher, Daniela; Steenmans, Christian Skjødt; Thygesen, Christian Bahne; Rønø, Birgitte; Friis, Stine (Frontiers in Immunology, 2023)
Tumor-specific mutations generate neoepitopes unique to the cancer that can be recognized by the immune system, making them appealing targets for therapeutic cancer vaccines. Since the vast majority of tumor mutations are patient-specific, it is crucial for cancer vaccine designs to be compatible with individualized treatment strategies. Plasmid DNA vaccines have substantiated the immunogenicity and tumor eradication capacity of cancer neoepitopes in preclinical models. Moreover, early clinical trials evaluating personalized neoepitope vaccines have indicated favorable safety profiles and demonstrated their ability to elicit specific immune responses toward the vaccine neoepitopes. In this study, we demonstrate how the addition of an antigen-presenting cell (APC) binding molecule to DNA-encoded cancer neoepitopes improves neoepitope-specific T-cell responses and the anti-tumor efficacy of plasmid DNA vaccines in preclinical cancer models. By fusing in silico predicted neoepitopes to molecules with affinity for receptors in the surface of APCs, such as chemokine (C-C motif) ligand 19 (CCL19), we designed an APC-targeting cancer vaccine able to induce more rapid T-cell responses and improve anti-tumor efficacy. Dose-response evaluation and longitudinal analysis of neoepitope-specific T-cell responses indicate that combining APC-binding molecules with the delivery of personalized tumor antigens holds the potential to improve the clinical efficacy of therapeutic DNA cancer vaccines.